2021
DOI: 10.3390/ijerph18031019
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Causal Process of Virtual Reality Tourism and Its Attributes in Terms of Their Effects on Subjective Well-Being during COVID-19

Abstract: In the landscape of Covid-19 pandemic, people’s well-being, to some extent, can be affected through virtual reality tourism because it has the opportunity to enhance their level of well-being and destination recovery. To verify this empirically an investigation was conducted among people who used Quanjingke, the largest tourism-related virtual reality website in China, during the pandemic. The specific the aim of this paper is to prove the effectiveness of virtual reality tourism in promoting people’s subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 58 publications
1
11
0
1
Order By: Relevance
“…The architecture of the tourist attraction information system, where objects can be seen in this system, is taken using a 360 0 camera. Then go through a Virtual reality geography process that users can later access via mobile or computer via the internet [15]. In the implementation phase, the author applies the design results made using the PHP and HTML languages.…”
Section: Figure 1 Research Methodsmentioning
confidence: 99%
“…The architecture of the tourist attraction information system, where objects can be seen in this system, is taken using a 360 0 camera. Then go through a Virtual reality geography process that users can later access via mobile or computer via the internet [15]. In the implementation phase, the author applies the design results made using the PHP and HTML languages.…”
Section: Figure 1 Research Methodsmentioning
confidence: 99%
“…In the COVID-19 pandemic, due to its limited access to the destination in person, tourist attachment with VR technology will help to keep the destination in mind and thus affect their future behavioral intention towards the destination (El-Said & Aziz, 2021). Li, Song, and Guo (2021)' study in a COVID-19 pandemic study, reveals that system attributes significantly impact on tourist perceived VR presence.…”
Section: Tourist Experience With Vrmentioning
confidence: 99%
“…Through a questionnaire survey and in-depth interviews, Chao [26] concluded that VRbased scientific experiments can expose people to events and objects that they would not otherwise experience in their everyday lives, thereby enhancing autonomous learning motivation. Li et al [27] reported that VR increased tourist wellbeing and positively affected perceived value. Chiao et al [28] examined the impact of virtual-tour-based platforms with different statistical indices (e.g., p-value and R-squared) for cultural tourism education.…”
Section: Information-technology-based Visualizationsmentioning
confidence: 99%